Risk factors for protein-energy malnutrition in pre-school shantytown children in São Paulo, Brazil - Ferrari, Alexandre Archanjo (1998)
OBJECTIVE: To investigate the health and nutritional conditions of people living in a shantytown in the city of São Paulo in order to identify risk factors for infant malnutrition. DESIGN: A retrospective cohort study. PARTICIPANTSs: Children living in a shantytown was conducted among children less than 72 months of age. METHODS: Home visits were made and information was collected regarding the risk factors for malnutrition. RESULTS: The prevalence of chronic malnutrition was 41.6% according to Gomez, 36.6% according to Waterlow, and 17.6% according to WHO. Risk factors for malnutrition, according to the weight-for-age index, included birthweight, presence of upper respiratory tract infections, number of pregnancies, number of births, maternal body mass index, birthplace of father, and home building material; according to the weight-for-height index, they included birthweight and maternal age at the time of birth; and according to the height-for-age index, they included the number of pre-natal medical visits, birthweight, maternal height, maternal body mass index, father's employment being unregistered, and maternal birthplace. An instrument for identifying children at risk of malnutrition was devised from these major risk factors for future malnutrition, which may then be applied to newly-born children.